Phase 1 trial evaluating cisplatin, gemcitabine, and veliparib in 2 patient cohorts: Germline BRCA mutation carriers and wild‐type BRCA pancreatic ductal adenocarcinoma. Issue 7 (16th January 2018) - O'Reilly, Eileen M.; Lee, Jonathan W.; Lowery, Maeve A.; Capanu, Marinela; Stadler, Zsofia K.; Moore, Malcolm J.; Dhani, Neesha; Kindler, Hedy L.; Estrella, Hayley; Maynard, Hannah; Golan, Talia; Segal, Amiel; et al.
Abstract : BACKGROUND: A phase 1 trial was used to evaluate a combination of cisplatin, gemcitabine, and escalating doses of veliparib in patients with untreated advanced pancreatic ductal adenocarcinoma (PDAC) in 2 cohorts: a germline BRCA 1/2‐mutated ( BRCA +) cohort and a wild‐type BRCA ( BRCA –) cohort. The aims were to determine the safety, dose‐limiting toxicities (DLTs), maximum tolerated dose, and recommended phase 2 dose (RP2D) of veliparib combined with cisplatin and gemcitabine and to assess the antitumor efficacy (Response Evaluation Criteria in Solid Tumors, version 1.1) and overall survival. METHODS: Gemcitabine and cisplatin were dosed at 600 and 25 mg/m 2, respectively, over 30 minutes on days 3 and 10 of a 21‐day cycle. Four dose levels of veliparib were evaluated: 20 (dose level 0), 40 (dose level 1), and 80 mg (dose level 2) given orally twice daily on days 1 to 12 and 80 mg given twice daily on days 1 to 21 (dose level 2A [DL2A]). RESULTS: Seventeen patients were enrolled: 9 BRCA + patients, 7 BRCA – patients, and 1 patient with an unknown status. DLTs were reached at DL2A (80 mg twice daily on days 1 to 21). Two of the 5 patients in this cohort (40%) experienced grade 4 neutropenia and thrombocytopenia. Two grade 5 events occurred on protocol. The objective response rate in the BRCA + cohort was 7 of 9 (77.8%). The median overall survival for BRCA + patients was 23.3 months (95% confidence interval [CI], 3.8‐30.2 months). The median overall survival for BRCA – patients was 11 months (95% CI, 1.5‐12.1 months). CONCLUSIONS: The RP2D of veliparib was 80 mg by mouth twice daily on days 1 to 12 in combination with cisplatin and gemcitabine; the DLT was myelosuppression. Substantial antitumor activity was seen in BRCA + PDAC. A randomized phase 2 trial is currently evaluating cisplatin and gemcitabine with and without veliparib for BRCA + PDAC (NCT01585805). Cancer 2018;124:1374‐82 . © 2018 American Cancer Society . Abstract : The recommended phase 2 dose of veliparib, combined with fixed‐dose cisplatin and gemcitabine, is 80 mg by mouth twice daily on days 1 to 12 of a 3‐week cycle. Substantial antitumor activity has been identified in a germline BRCA ‐mutated patient population with untreated advanced pancreatic adenocarcinoma.